Shared perceptions of flavored cigarette pack design among young adults who smoke in Mexico and the Philippines - Graziele Grilo+; Jennifer L. Brown+; Joanna E. Cohen; Katherine Clegg Smith (Tobacco Induced Diseases)
Introduction Tobacco industry documents reveal companies’ knowledge of a similar young adult market across countries in terms of attitudes and lifestyle aspirations. Some tobacco companies, therefore, use similar marketing approaches across different jurisdictions. We examined young adults’ perceptions of flavored cigarette packs, including those containing flavor capsules, in Mexico and the Philippines.